(untitled) (Journal of the College of Basic Education, 2026)
The aim of this research was to classify 200-meter freestyle swimmers according to the genetic markers of monocarboxylate transporters (MCT4), and to design core stability training programs tailored to the characteristics of 200-meter freestyle swimmers based on their MCT4 genotypes. The study also sought to examine the impact of genetic markers as indicators for guiding core stability training in relation to swimmers’ specificity in arm muscular endurance, post-exercise blood lactate concentration, and 200-meter freestyle performance, The experimental method was applied using two experimental groups of swimmers classified by their MCT4 genotypes (AT and AA, respectively). Research tests included physical, laboratory, and performance assessments. A core stability-training program was designed and implemented over a total of 24 training units across 8 weeks, at a frequency of three sessions per week, applied to the swimmers in both groups. Data were processed using the SPSS statistical package. The results indicated that differences in the MCT4 genetic markers, specifically the AA and AT genotypes, played a role in how swimmers responded to core stability training of the trunk muscles. These differences were reflected in the degree of improvement in arm muscular endurance, the reduction of post-exercise blood lactate concentration, and enhancement in 200-meter freestyle performance. Swimmers with the AA genotype of the MCT4 gene showed greater improvements in arm muscular endurance, greater reductions in post-exercise blood lactate, and better enhancements in 200-meter freestyle performance compared to those with the AT genotype, when subjected to core stability training. The researcher therefore recommends the necessity of applying practical approaches from molecular genetics research in athlete training, utilizing them to design individualized training programs. Coaches should be provided with greater knowledge of the importance of genetic markers, particularly MCT4, in order to better support their training plans based on physiological principles underlying genetic differences. Furthermore, sports clubs are encouraged to adopt modern molecular genetics laboratories to classify 200-meter freestyle swimmers by their MCT4 genotypes, given the critical role of such classifications in planning and applying training according to the principles of sports training physiology in swimming.